Competitiveness analysis and development strategies for 33 Indonesian provinces - Tan, Khee Giap; Amri, Mulya; Low, Linda; Tan, Kong Yam (New Jersey : World Scientific, 2013)
'Indonesia is on the cusp of transformative take-off, poised to become a major economic power not just in Asia, but also on the global-stage. This book is a pioneering attempt in comprehensively assessing all attributes, conditions and policies for 33 Indonesian provinces and Indonesia's trajectory as an emerging middle power. It contains papers and data-sets presented in July 2012, at ACI's signature annual conference. The information that was shared at the conference and presented in the book posit a future where tens of millions of Indonesians will be lifted out of poverty to become a self-sustaining middle-class, which will in turn drive the country into a global leadership role in the 21st century. It is a compelling value-added proposition for policy simulations enabling policy-makers to identify relative weaknesses, strengths, threats and opportunities of individual 33 provinces, guiding them to prioritise areas in crafting policies and development strategies'--
Keywords: Indonesian provinces -- Economic policy -- 21st century; Economic development -- Indonesia -- Provinces; Competition -- Indonesia -- Provinces; Indonesia -- Economic conditions -- Regional disparities